Implications of Older Adults' Attributions for Young Adults' Attitudes to Aging: A Vignette Study. (January 2023) - Fowler, Craig; Bernhold, Quinten
The present study was grounded in the revised communicative ecology model of successful aging (CEMSA) and examined whether brief, passing remarks made by older adults about aging influence both young adults' aging efficacy and their expectations regarding aging. Young adult participants ( n  = 322) were randomly assigned to read a single vignette. In the vignette an older adult invoked either a negative age-based reason, a non-age-based reason, or a positive age-based reason to account for behavior that could be taken to reflect age-related stereotypes pertaining to physical decline, cognitive decline, or aversion to technology. Analyzes revealed that participants who read the positive age-based accounts perceived the aging process to have been portrayed more favorably. Consequently, they reported higher levels of positive affect about aging which translated into their feeling more efficacious about managing their own aging, and into having more positive expectations regarding aging in general.